CYTOTOXICITY OF STEM EXTRACTS OF SELECTED CASSIA SPECIES AGAINST HELA AND BREAST CANCER CELL LINES IN VITRO - Deshpande, Surekha R; NAIK B, SHANKAR (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The use of plants for medicinal remedies is an integral part of the Indian cultural life, and the traditional background of Indian medicine shows widespread use of plant products in cancer treatment. In this study, stem extracts of some selected Cassia species have been evaluated for their cytotoxic activities under in vitro conditions. Methods: The stems were shade dried at room temperature. The dried and coarsely powdered plant material were extracted with petroleum ether (60-80°C), chloroform, and ethanol using soxhlet apparatus. The cytotoxicity was evaluated by [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay. Results: Stem extracts of three Cassia species, viz., Cassia glauca, Cassia Obtusifolia, and Cassia sophera have been evaluated for their cytotoxic activities with chloroform, ethanol and pet ether against HeLa and breast cancer cell lines. Among the three different solvents used at different concentrations, the chloroform extracts of all Cassia species exhibited maximum cytotoxicity (%) against both cell lines. The CTC50 values are revealed the cytotoxic potential of C. glauca chloroform extracts against HeLa cell line and breast cancer cell lines with CTC50 values 180.00±3.0 and 146.67±0.5, respectively. Chloroform extracts of C. Obtusifolia and C. sophera showed maximum activity against HeLa (380.00±1.1 and 800.00±1.7, respectively) and breast cancer cell lines (310.00±1.1 and 633.33±0.6). Conclusion: The results of this study demonstrate the potent cytotoxic activity of chloroform extracts of stems of Cassia species against HeLa and Breast cancer cell lines. Keywords: Cassia, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, Cytotoxicity, HeLa, Breast cancer.